(3JYdjb Ydi CdajI Hf eGdcs - (3HgGA GdOjf YHO Gddg Hf YHO GdQMef Hf Ybjd GdTGaYjs; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI CeG HYO MeO Gddg Ydi fYeGFI agPG JYdjb efj LeYJg Ydi SHjd GdahGFO dLeGd GdOjf Hf eGdc HGH TQM GdcdeI hGdcdGe heG jJYdb HgeG s
(3BNQgG (B:s
(3ef BNQ GdehLhO Hg Ef dGJ GdSGYI SGYI caQGAI HYVge (B( (3hdG J Mjf efGU (B) (3HQaY GdNjQ dG HcSQ efGU s
(3Vef eLehY , JQJjHgG (B: 2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B31 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B239 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B135s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3eJaQbGJs